Media Pembelajaran Interaktif Menggunakan Metode Luther Sutopo Tentang Pengelompokan Hewan Berdasarkan Jenis Makanannya - R. Romiz Aisy (Sekolah Vokasi, Universitas Sebelas Maret, 2024)
A learning method that is easy for children to understand can enhance their ability to grasp the material being taught. The previous method used to introduce children to animal classification was through books. However, using books to explain animal classification to children is less effective due to the limited interactivity between children and the material provided. Interactive learning media is a solution that can be used to increase interactivity and help children better understand the given material. This study employs the Luther-Sutopo method and aims to develop interactive learning media. The result is an interactive learning tool about animal classification based on their diet, featuring quizzes, images, games, and interactive videos.